2016
DOI: 10.1016/j.jpha.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of residual crosslinking agent content in UV cross-linked poly(ethylene oxide) hydrogels for dermatological application by gas chromatography

Abstract: Acrylates have been widely used in the synthesis of pharmaceutical polymers. The quantitation of residual acrylate monomers is vital as they are strong irritants and allergens, but after polymerization, are relatively inert, causing no irritation and allergies. Poly(ethylene oxide) (PEO) hydrogels were prepared using pentaerythritol tetra-acrylate (PETRA) as UV crosslinking agent. A simple, accurate, and robust quantitation method was developed based on gas chromatographic techniques (GC), which is suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…PETRA was then added into the premixed gel, and the entire mixtures were further stirred for 8 h until homogeneous. The cross-linker concentration was fixed at 5% w / w , as this concentration was found to be optimum in producing gel films with good mechanical properties [ 4 ], as well as being safe for dermatological application [ 6 ]. The viscous mixture was allowed to stand for 16 h to remove entrapped air bubbles before it was cast onto a glass tile (dimension = 30 cm × 30 cm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PETRA was then added into the premixed gel, and the entire mixtures were further stirred for 8 h until homogeneous. The cross-linker concentration was fixed at 5% w / w , as this concentration was found to be optimum in producing gel films with good mechanical properties [ 4 ], as well as being safe for dermatological application [ 6 ]. The viscous mixture was allowed to stand for 16 h to remove entrapped air bubbles before it was cast onto a glass tile (dimension = 30 cm × 30 cm).…”
Section: Methodsmentioning
confidence: 99%
“…The principal concern of this cross-linking method is the presence of residual acrylate monomer. However, the inclusion of pentaerythritol tetraacrylate (PETRA) as cross-linking agent was evaluated to be safe for dermatological application as long as it is within the maximum acceptable limit of 10% w / w [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, PT has been used as a crosslinker of polyethylene oxide (PEO) hydrogel films synthesised using UV radiation [29]. Other studies suggest that when PT absorbs energy from UV photons, its acrylate group generates reactive-free radicals, which initiates the crosslinking of repeated units of the polymer with PT radicals via recombination [29]. However, it is difficult to induce the free radicals on PT without adding a photoinitiator.…”
Section: Crosslinking Mechanismmentioning
confidence: 99%
“…Therefore, it is important to conduct residual content analysis for PT in the optimised hydrogel films and, subsequently, to adjust the PT amount in the formulation if necessary, so as to ensure that there is no unreacted PT and to establish the biocompatibility of our novel hydrogel films. We will conduct this analysis using the method we previously developed for the quantification of residual PT in PEO hydrogel films [17]. Toxicological studies of PT and similar crosslinking agents on guinea pigs showed that PT had a lower sensitising effect [18].…”
Section: Ftir Spectral Analysismentioning
confidence: 99%